2003
DOI: 10.1017/s0031182003003901
|View full text |Cite
|
Sign up to set email alerts
|

Lead concentrations in Hymenolepis diminuta adults and Taenia taeniaeformis larvae compared to their rat hosts (Rattus norvegicus) sampled from the city of Cairo, Egypt

Abstract: Concentrations of lead, determined by electrothermal atomic absorption spectrometry, were compared between the cestodes Hymenolepis diminuta and Taenia taeniaeformis and its host rat (Rattus norvegicus). Rats were sampled at 2 sites, which differed in respect to lead pollution as quantified from road dust, adjacent to the city of Cairo, Egypt. Comparing lead levels among host tissues and the parasites the significantly highest accumulation was found in H. diminuta, followed by rat kidney and larvae of T. taeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
21
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 15 publications
7
21
1
Order By: Relevance
“…According to our results, G. arfaai presented 6, 20 and 24 times more lead than that detected in the kidney, liver and muscle of A. sylvaticus from not especially polluted areas of Catalonia. These values are comparable with those (6 and 29-fold higher lead levels in H. diminuta as compared with kidney and liver of R. rattus) reported by Sures et al (2003) in Helban, a highly polluted area of Cairo, Egypt. Thus, according these and the present results, it seems that cestodes of rodents may be considered suitable sentinel organisms of environmental lead pollution.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…According to our results, G. arfaai presented 6, 20 and 24 times more lead than that detected in the kidney, liver and muscle of A. sylvaticus from not especially polluted areas of Catalonia. These values are comparable with those (6 and 29-fold higher lead levels in H. diminuta as compared with kidney and liver of R. rattus) reported by Sures et al (2003) in Helban, a highly polluted area of Cairo, Egypt. Thus, according these and the present results, it seems that cestodes of rodents may be considered suitable sentinel organisms of environmental lead pollution.…”
Section: Discussionsupporting
confidence: 88%
“…Thus, according these and the present results, it seems that cestodes of rodents may be considered suitable sentinel organisms of environmental lead pollution. Sures et al (2003) reported a particularly high variability in lead concentrations in H. diminuta with relative standard deviations ranging between 112% and 135%. These authors also emphasised the need to standardise the sampling procedures for cestodes used as sentinel species, and proposed the use of worms of approximately the same length, thus reflecting a measure of age.…”
Section: Discussionmentioning
confidence: 99%
“…Also considering the terrestrial compartment, the system Rattus norvegicus/Hymenolepis diminuta was the first host/cestode system to be evaluated for its possible capacity of Pb accumulation both under experimental conditions (Sures et al 2002) and in the field (Sures et al 2003). The latter was performed in the city of Cairo (Egypt) and the evaluated host-parasite model was confirmed as a promising bioindicator system for Pb in urban ecosystems (Sures et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The latter was performed in the city of Cairo (Egypt) and the evaluated host-parasite model was confirmed as a promising bioindicator system for Pb in urban ecosystems (Sures et al 2003). Other subsequent field studies included cestode parasites of rodents (Apodemus sylvaticus; Torres et al 2004Torres et al , 2006, lagomorphs (Oryctolagus cuniculus; Eira et al 2005) and terrestrial urban birds (Columba livia; Torres et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation